Rural and regional maternity managers' and educators' views of the Maternity and Newborn Emergencies (MANE) education program in Victoria, Australia: a qualitative descriptive study - Stefanie A Zugna; Helen L McLachlan; Meabh Cullinane; Michelle Newton; Della A Forster (BMC, 2024)
Abstract Background Australia has one of the lowest perinatal morbidity and mortality rates in the world, however a cluster of perinatal deaths at a regional health service in the state of Victoria in 2015 led to state-wide reforms, including the introduction of the Maternity and Newborn Emergencies (MANE) program. MANE was a 2-day interprofessional maternity education program delivered by external expert facilitators to rural and regional Victorian maternity service providers. An independent evaluation found that the MANE program improved the confidence and knowledge of clinicians in managing obstetric emergencies and resulted in changes to clinical practice. While there is a large volume of evidence that supports the use of interprofessional education in improving clinicians' clinical practice, the impact of these programs on the overall safety culture of a health service has been less studied. Managers and educators have an important role in promoting the safety culture and clinical governance of the heath service. The aim of this study, therefore, was to explore Victorian rural and regional maternity managers' and educators' views and experiences of the MANE program. Methods Maternity managers and educators from the 17 regional and rural health services across Victoria that received the MANE program during 2018 and 2019 were invited to participate. Semi-structured interviews using mostly open-ended questions (and with a small number of fixed response questions) were undertaken. Qualitative data were transcribed verbatim and analysed thematically. Descriptive statistics were used for quantitative data. Results Twenty-one maternity managers and educators from the 17 health services participated in the interviews. Overall, participants viewed the MANE program positively. Four themes were identified: the value of external facilitation in providing obstetric emergency training; improved awareness and understanding of clinical governance; improved clinical practice; and the importance of maintaining the program. Participants agreed that MANE had improved the confidence (94%) and skills (94%) of clinicians in managing obstetric emergencies, as well as confidence to escalate concerns (94%), and most agreed that it had improved clinical practice (70%) and teamwork among attendees (82%). Conclusion Maternity managers and educators were positive about MANE; they considered that it contributed to improving factors that impact the safety culture of health services, with delivery by external experts considered to be particularly important. Given the crucial role of maternity managers and educators on safety culture in health services, as well in program facilitation, these findings are important for future planning of maternity education programs across the state. Trial registration Trial registration was not required for this study.